The Implementation of TBLT in Teaching Speaking for Students in Vocational High School - Putri Febrianti; Ririn Pusparini (Journal of Innovative and Creativity, 2025)
Proficiency in English, especially in speaking, is crucial for vocational high school students aiming to compete in the global workforce. However, many students encounter challenges in effective communication. Task-Based Language Teaching (TBLT), which focuses on meaningful communication through meaningful tasks, offers encouraging solution. This research aims to describe how TBLT is implemented in teaching speaking for vocational high school students and to know the students’ speaking performance after using this method. This research is a basic interpretative qualitative design, the research was conducted with eleventh-grade students of DPIB 1 and an English teacher at one of vocational high school in Surabaya. The data in this research are observation sheet and performance assessments using a rubric. the data are analyzed descriptively to answer the research questions. The result of the observation showed that the implementation of this approach was in line with three stages of TBLT in teaching speaking. The teacher successfully designed tasks relevant to the students need and showed increased the students speaking skill. Analysis of the students speaking performance indicated notable helps in pronunciation and vocabulary. While fluency and grammar also showed progress, they require further development. Overall, the implementation of TBLT helped the students in speaking English. It could be shown in the result of students performances. This research underscores TBLT’s potential to enhance speaking proficiency in vocational contexts through relevant and authentic tasks.